A REVIEW OF 120 CASES OF DACRYOCYSTORHINOSTOMIES (DUPUY DUTEMPS AND BOURGUET TECHNIQUE) - Zaman, Mir; Babar, Tariq Farooq; Saeed, Nasir (Journal of Ayub Medical College Abbottabad, 2003)
Background: The study was conducted at the DHQ hospital Lakki Marwat from Jan, 1999 to Dec, 2002 to assess the intra and postoperative complications and success rate of external dacryocystorhinostomy (DCR) with suturing of the bridge between anterior flaps of nasal mucosa and lacrimal sac with the muscle layer. Method: We operated upon 120 patients suffering from chronic dacryocystitis (CDC). Females were 81 (67. 5%) and males were 39 (32.5%). Majority of the patients were between the age group 40 to 60 years. Indications for dacryocystorhinostomy (DCR) were epiphora, acute on chronic dacryocystitis and a mucocele. All the cases were operated under local anaesthesia with external approach and only anterior flap suturing and engaging it in the muscle layer. These patients were followed for a period of six months. Results: The overall success rate was 98.33%. The successful outcome was defined as symptomatic relief from epiphora and dacryocystitis and a patent nasolacrimal duct upon syringing. Conclusions: Dacryocystorhinstomy is a safe procedure under local anaesthesia. It is associated with minimal complications, which can be easily managed. This technique has a very high success rate and a short learning curve. Keywords: External dacryocystorhinostomy, Chronic dacryocysttitis, Epiphora.